Analisis Creative Problem Solving (CPS) pada Anak Berbakat (Gifted And Talented Children) di Usia Prasekolah: Analysis Of Creative Problem Solving in Gifted and Talented Children at Preschool Age - Widi Febriani; Syafrimen Syafril; Erfha Nurrahmawati (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
Gifted & Talented Children demonstrate abilities or potential that are far above average in one or more specific areas, such as academics, arts, or sports. The development of Creative Problem-Solving Skills in gifted children is key to forming the foundation of problem-solving abilities that will support children throughout their lives. This study examines how the development of CPS in gifted children at preschool age through reputable articles. This study uses a systematic literature review method with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow. The data obtained were analyzed using an Interactive qualitative data analysis model with the help of NVIVO 12 software. Literature was taken from reputable databases such as Scopus, Springer, Sciendirect, DOAJ and Google Scholar databases. There are 4 steps to conducting a literature review, namely: identifying the topic/issue to be reviewed (identification), selecting similar articles (screening), analyzing literature that meets the appropriate requirements (eligibility), compiling a review writing (included). The results of the study showed that there are several factors that influence the development of CPS in gifted children at preschool age, including family environment, parenting patterns, learning methods obtained at school, social interactions with peers, and psychological factors including emotional intelligence and motivation.   ABSTRAK Anak berbakat (Gifted & Talented Children) menunjukkan kemampuan atau potensi yang jauh di atas rata-rata dalam satu atau lebih pada bidang tertentu, seperti akademik, seni, atau olahraga. Perkembangan Keterampilan Pemecahan Masalah Kreatif (Creative Problem Solving) pada anak berbakat menjadi kunci untuk membentuk dasar kemampuan pemecahan masalah yang akan mendukung anak sepanjang hidup. Penelitian ini mengkaji bagaimana perkembangan CPS anak berbakat pada usia prasekolah melalui artikel bereputasi. Penelitian ini menggunakan metode tinjauan literatur sistematik (Systematic Literature Review) dengan alur PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Data yang diperoleh dianalisis menggunakan model analisis data kualitatif Interaktif dengan bantuan perangkat lunak NVIVO 12. Literatur diambil melalui database beriputasi seperti dari database Scopus, Springer, Sciendirect, DOAJ dan Google Scholar. Ada 4 langkah untuk melakukan tinjauan literatur yaitu: mengidentifikasi topik/isu yang akan di telaah (identification), memilih artikel yang sejenis (screening), menganalisis literatur yang sesui persyartan yang sesuai (eligibility), menyusun penulisan review (included). Hasil penelitian menunjukkan bahwa terdapat beberapa factor yang mempengaruhi perkembangan CPS anak berbakat pada usia prasekolah diantaranya lingkungan keluarga, pola asuh, metode pembelajaran yang didapatkan disekolah, interaksi sosial dengan teman sebaya, dan faktor psikologis termasuk kecerdasan emosional dan motivasi.